Cytoprotective activated protein C averts Nlrp3 inflammasome-induced ischemia-reperfusion injury via mTORC1 inhibition - Nazir, Sumra; Gadi, Ihsan; Al-Dabet, Moh'd Mohanad; Elwakiel, Ahmed; Kohli, Shrey; Ghosh, Sanchita; Manoharan, Jayakumar; Ranjan, Satish; Bock, Fabian; Braun-Dullaeus, Ruediger C; Esmon, Charles T; Huber, Tobias B; et al. (Blood, 2017)
Cytoprotection by activated protein C (aPC) after ischemia-reperfusion injury (IRI) is associated with apoptosis inhibition. However, IRI is hallmarked by inflammation, and hence, cell-death forms disjunct from immunologically silent apoptosis are, in theory, more likely to be relevant. Because pyroptosis (ie, cell death resulting from inflammasome activation) is typically observed in IRI, we speculated that aPC ameliorates IRI by inhibiting inflammasome activation. Here we analyzed the impact of aPC on inflammasome activity in myocardial and renal IRIs. aPC treatment before or after myocardial IRI reduced infarct size and Nlrp3 inflammasome activation in mice. Kinetic in vivo analyses revealed that Nlrp3 inflammasome activation preceded myocardial injury and apoptosis, corroborating a pathogenic role of the Nlrp3 inflammasome. The constitutively active mutation abolished the protective effect of aPC, demonstrating that Nlrp3 suppression is required for aPC-mediated protection from IRI. In vitro aPC inhibited inflammasome activation in macrophages, cardiomyocytes, and cardiac fibroblasts via proteinase-activated receptor 1 (PAR-1) and mammalian target of rapamycin complex 1 (mTORC1) signaling. Accordingly, inhibiting PAR-1 signaling, but not the anticoagulant properties of aPC, abolished the ability of aPC to restrict Nlrp3 inflammasome activity and tissue damage in myocardial IRI. Targeting biased PAR-1 signaling via parmodulin-2 restricted mTORC1 and Nlrp3 inflammasome activation and limited myocardial IRI as efficiently as aPC. The relevance of aPC-mediated Nlrp3 inflammasome suppression after IRI was corroborated in renal IRI, where the tissue protective effect of aPC was likewise dependent on Nlrp3 inflammasome suppression. These studies reveal that aPC protects from IRI by restricting mTORC1-dependent inflammasome activation and that mimicking biased aPC PAR-1 signaling using parmodulins may be a feasible therapeutic approach to combat IRI.